2021
DOI: 10.1002/smll.202106383
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Proton Therapy Efficiency by Noble Metal Nanoparticles Is Driven by the Number and Chemical Activity of Surface Atoms

Abstract: Proton‐based radiotherapy is a modern technique for the treatment of solid tumors with significantly reduced side effects to adjacent tissues. Biocompatible nanoparticles (NPs) with high atomic numbers are known to serve as sensitizers and to enhance treatment efficacy, which is commonly believed to be attributed to the generation of reactive oxygen species (ROS). However, little systematic knowledge is available on how either physical effects due to secondary electron generation or the particle surface chemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 93 publications
(190 reference statements)
6
39
1
Order By: Relevance
“…We thus concluded that (i) proton irradiation led to lower nanoparticle excitation compared to X-rays, and (ii) the energy spectrum (150 kVp vs. 6 MV) of the X-rays had an influence on the electron–hole pair generation for high- Z nanoparticles (HfO 2 and WO 3 ) but not for TiO 2 nanoparticles. Au nanoparticles also possess the ability to generate ROS under X-ray 41 , 47 , 48 or proton 49 irradiation. Using 150 kVp X-rays and acellular ROS assays, Au NPs were found to generate additional •OH radicals 48 .…”
Section: Resultsmentioning
confidence: 99%
“…We thus concluded that (i) proton irradiation led to lower nanoparticle excitation compared to X-rays, and (ii) the energy spectrum (150 kVp vs. 6 MV) of the X-rays had an influence on the electron–hole pair generation for high- Z nanoparticles (HfO 2 and WO 3 ) but not for TiO 2 nanoparticles. Au nanoparticles also possess the ability to generate ROS under X-ray 41 , 47 , 48 or proton 49 irradiation. Using 150 kVp X-rays and acellular ROS assays, Au NPs were found to generate additional •OH radicals 48 .…”
Section: Resultsmentioning
confidence: 99%
“…Next to these unintended use scenarios, nanoparticle-induced ROS is further discussed as one of the most critical pathways in the anti-tumor efficiency of sensitizers in irradiation therapy 3 . Here, a recent study suggested a correlation between therapy-enhancing effects of Pt and Au nanoparticles in proton therapy and catalytic surface reactions 4 . Another important research field is single atom catalysts which are discussed as relevant materials for biomedical applications 5 .…”
Section: Introductionmentioning
confidence: 91%
“…As we have already demonstrated that different sterilization methods have a significant impact on the stability of colloidal AuNPs, it is critical to investigate how different NP sterilization methods affect PT enhancement, as a case study. According to a recent report, 16 both the surface dose and surface chemistry of the NPs play an inevitable role in ROS production in NP-assisted irradiation therapy, and hence any processing of the particles that may hamper the surface properties should be excluded. Here, particle growth may reduce the specific surface area, thus decreasing the expected boosting effects of NPs in proton treatment.…”
Section: Sterilization Of Aunps 331 Steam Sterilization (Autoclaving)mentioning
confidence: 99%
“…This again underlines that for smaller AuNPs, sterile filtration is more effective than the steam sterilization technique from the application point of view, considering the scaling of ROS generation with the available particle surface area. 16 A decrease in the ROS generation could also be attributed to defect healing through the surface restructuring through coalescence, 101 as defects are known for their enhancing effect in, for example, the oxygen evolution reaction, which leads to the generation of ROS. 102 The immediate cooling of generated particles in LAL due to the surrounding liquid often leads to the kinetic stabilization of defect-rich and metastable phases.…”
Section: Sterilization Of Aunps 331 Steam Sterilization (Autoclaving)mentioning
confidence: 99%
See 1 more Smart Citation